A personal stand : observations and opinions from a freethinking roughneck - Adkins, Trace (Villard, 2007)
Country music star Adkins isn't known for holding back what's on his mind. And if his album sales are any indication, when Trace talks, people listen. Here, he delivers his maverick manifesto on politics, personal responsibility, fame, parenting, being true to yourself, hard work, and the way things ought to be.--From publisher description.